Coating metal–organic frameworks on plasmonic Ag/AgCl nanowire for boosting visible light photodegradation of organic pollutants. Issue 5 (24th January 2022) - Chen, Xi; Zhang, Yanshuang; Kong, Xiangyun; Yu, Bowen; Wang, Shuaiyin; Xu, Wenyuan; Fang, Zhili; Zhang, Jiali; Yao, Kun; Liu, Yongxin
Abstract : A photoactive metal–organic framework, MIL-100(Fe), with controllable thickness was coated on plasmonic Ag/AgCl nanowire for boosting the visible light photodegradation of rhodamine B and tetracycline hydrochloride. Abstract : Photoactive metal–organic frameworks, MIL-100(Fe), with controllable thickness are coated on plasmonic Ag/AgCl nanowire, for boosting visible light photodegradation of rhodamine B and tetracycline hydrochloride. The morphology and composition of the obtained nano-heterostructure were investigated in detail by SEM imaging, TEM imaging, XRD patterns, FT-IR spectra, N2 adsorption–desorption curves and TGA patterns. Photoelectric performance test suggested that a Z-scheme photocatalysis system for efficient transfer of photogenerated charge carriers was established between MIL-100(Fe) and plasmonic Ag/AgCl nanowire.